A Molecular study of the Cabbage White Butterfly (Pieris rapae) Infesting Cabbage (Brassica oleracea var. capitata) in Iraq. - Sabhan Abdulrahman, Sarah (University of Thi-Qar Journal of agricultural research, 2025)
A molecular study was carried out on the cabbage white butterfly Pieris rapae. The mitochondrial cytochrome c oxidase subunit I (COXI) gene was targeted using the Polymerase Chain Reaction (PCR) technique after extracting genomic DNA from the insect specimens. The nucleotide sequences of the COXI gene amplification products were determined. The obtained sequences were aligned and compared with previously registered sequences in the National Center for Biotechnology Information (NCBI) database. Subsequently, the Iraqi isolate was registered in the NCBI database under the name Pieris rapae isolate Tikrit-1 (Iraq) with the accession number PV012487. The results revealed a 100% sequence identity between the Iraqi and the Chinese isolates Pieris rapae isolate pr1 (accession number OR491929.1), indicating a high degree of genetic similarity. The calculated genetic distance between the Iraqi isolate and other international isolates was notably low, recorded at 0.0015. A phylogenetic tree was constructed using MEGA 11 to assess the genetic relationships. The analysis demonstrated a close genetic affiliation between the Iraqi isolate and global isolates of the same species, confirming the genetic relatedness of P. rapae populations across different geographical regions.